Biliary sludge - I. N. Grigorieva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2009)
The aim of review. To describe prevalence, basic mechanisms, risk factors and variants of course of biliary sludge, and methods of its treatment.Original positions. Biliary sludge consists of inhomogeneous structures, suspension and clots in bile. Its prevalence in general population ranges 1,7 to 4%, and is 7,5% of patients with gastroenterological complaints. Pathogenic mechanisms of biliary sludge include following: decrease of bile acids synthesis, disorders of neurohumoral synchronization of gallbladder contractility, resulting in its hypotony, qualitative changes of pronucleator composition of biliary sludge, in particular – glycosaminoglycans, accelerating process of vesicles coalescence in bile, that in general promotes increase of its lithogenicity. There are some classifications of this disease based on etiology, sonographic pattern and chemical composition of sludge. Cholelithiasis, diabetes mellitus, cholestasis of a various origin, pregnancy, intake of some medicines (ceftriaxone, octreotide, clofibrate, calcium-containing agents, etc.), sickle-cell anemia, etc. are known as major risk factors. Course of biliary sludge can be asymptomatic, with signs of biliary dyspepsia or with complications including pancreatitis, constrictive papillitis, acute cholangitis, etc. The most effective treatment agent is ursodeoxycholic acid, if of biliary sludge is combined to nonfunctioning gallbladder surgical intervention is indicated.Conclusion. Gastroenterological patients, and patients with risk factors of biliary sludge should undergo investigation for revealing this disease, well-timed prescription treatment and early prophylaxis of complications.